A Flexible Non-Enzymatic Hydrogel-Assisted Electrochemical Sensor: Wireless, Sensitive, and Selective Uric Acid Detection for Home Monitoring - Tasca-Gottardo, F; Tasca-Gottardo, F (Elsevier Inc., 2024)
A smartphone-enabled, wireless, and battery-free electrochemical sensor equipped with electroactive poly (3,4-ethylenedioxythiophene):poly(styrenesulfonate)/polyvinyl alcohol (PEDOT:PSS/PVA) hydrogel composites, was developed for the non-enzymatic assessment of uric acid (UA) concentrations in human serum and wound exudate. The sensor was constructed with the aid of simple and sustainable modification techniques, such as drop-casting and crosslinking via a green freezing–thawing protocol. Gold nanoparticles (AuNPs) and the PEDOT:PSS/PVA electroactive hydrogel were employed to increase the surface area of the sensor and sample interactions, which improved the sensitivity and specificity for UA detection in the clinical range of 10–1,000 µM, with a detection limit of 0.05 mg/dL in addition to biocompatibility (L-929 cell viability > 90 %). In human serum and wound exudate samples, the prepared sensor demonstrated a good correlation for UA detection when compared to ISO15189 accredited medical laboratory measurements (Pearson correlation coefficient (r) = 0.97 and r = 0.98, respectively). The UA sensor was integrated with the flexible near field communication (NFC) circuit, and demonstrated the feasibility of measuring UA in human serum and wound exudate with results that were consistent with uricase enzymatic determination (p-value > 0.05). The sensor s wearability was demonstrated by a recovery rate of 101–109 % UA detection when bending on the IV training arm. This NFC UA sensing device can serve as a good alternative platform for self–UA monitoring, along with the potential for developing a smart wound dressing for wound management. © 2024 Elsevier B.V.